BUDGET PARTICIPATION AND BUDGETARY SLACK: THE MEDIATING EFFECT OF AUTONOMOUS BUDGET MOTIVATION - Novi Lailiyul Wafiroh; Fadlil Abdani; Fajar Nurdin (UNIB Press, 2020)
The purpose of our research is to provide empirical evidence of what and how participation in budgeting relates to the creation of budgetary slack conducted by managers through autonomous budget motivation. This research is expected to contribute to research and practice in the field of management accounting. Hypothetical testing is done empirically by collecting data through questionnaire dissemination surveys in various companies located in East Java. Data testing is performed with the help of the SmartPLS 3.0 app. The results of the data analysis showed that increased participation in budget preparation by managers from various departments led to a decrease in the creation of budgetary slack by managers. Nevertheless, the data test results were unable to prove that autonomous budget motivation was able to act as a mediation variable in the relationship between budget participation and budgetary slack. The results of the study indicate that only by actively participating in the budget preparation process, can directly reduce the tendency of employees to create budgetary slack without waiting for the high motivation of autonomous budgets that employees have first. Keywords: Budget participation, Budgetary Slack, Autonomous Budget Motivation